Defining and applying measures of distance between specifications. - Jilani, L.L (IEEE Transactions on software engineering)
Echoing Louis Pasteur's quote, we submit the premise that it is advantageous to define measures of distance between requirements specifications because such measures open up a wide range of possibilities both in theory and in practice. The authors present a mathematical basis for measuring distances between specifications and show how their measures of distance can be used to address concrete problems that arise in the practice of software engineering